A Review of the Control of Aedes aegypti (Diptera: Culicidae) in the Continental United States. Issue 1 (23rd August 2020) - McGregor, Bethany L; Connelly, C Roxanne
Abstract: Aedes aegypti (L) is an anthropophilic mosquito involved in the transmission of a variety of viral pathogens worldwide including dengue, chikungunya, yellow fever, and Zika viruses. This species, native to Africa, is well established in the continental U.S. (CONUS) and occasionally contributes to localized outbreaks of viral diseases. In the last seven decades, mosquito control programs in the CONUS have been focused on vectors of eastern equine encephalitis, St. Louis encephalitis, and West Nile viruses, as well as nuisance species. Aedes aegypti receives little control focus except during outbreak periods, which has led to a lack of information on appropriate and effective control options targeting Ae. aegypti in the CONUS. As such, in the event of an Ae. aegypti -borne arboviral outbreak in the CONUS, there are limited evidence-based control recommendations or protocols in place. Autochthonous outbreaks of Ae. aegypti -borne pathogens have occurred recently in the CONUS, including dengue outbreaks in 2010 and 2013, a chikungunya outbreak in 2014, and the 2016 outbreak of Zika virus. The increasing frequency of Ae. aegypti -borne outbreaks necessitates increased attention and research on control of this species to prevent and mitigate future outbreaks. This review consolidates and synthesizes the available literature on control of Ae. aegypti, specifically within the CONUS, focusing on data generated through operational applications as well as field and semifield experiments. The purpose of this review is to identify and highlight areas where additional research is needed. The review covers chemical control and insecticide resistance, biological control, source reduction, trapping, and alternative techniques.